PERANCANGAN DAN IMPLEMENTASI ANIMATED STICKER SEBAGAI MEDIA EDUKASI MENGENAI COVID-19 DENGAN MENGGUNAKAN METODE MDLC - Rena Indira Putri; Jimmy Pratama (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2021)
The whole world is in an uproar with the COVID-19 pandemic, this new categorized corona virus has made people panic and restless, including in Indonesia. The number of confirmed cases of COVID-19 continues to increase. So that implementing health protocols is the most important thing to do. Various methods of prevention and handling are carried out to suppress thespread of this virus, one of which is through media education and information to the public about various ways that can be done to prevent transmission of the corona virus. This literature study provides stages from design to implementation of animated stickers as educational media about COVID-19. The result of this literature study is the formation of animated stickers that can be used for educational media and the delivery of information on various preventive measures that can be taken by the community to break the chain of the spread of the corona virus. By using informative and interesting visual media, of course, it can make people read carefully and facilitate the process of public understanding. Thus, it can be concluded that the use of animated sticker visual media with the MDLC method can facilitate the public in receiving clearer and easier to understand information.